Mythocritical study between Plutarch’s Paralell Lives and El robo de las sabinas (The Abduction of the Sabine Women) by Juan Coello y Arias, Francisco de Rojas Zorrilla and Antonio Coello Ochoa (Minerva, 2021)
Starting from myth criticism, the theoretical foundation on which this study is structured, the paper aims to analyse whether Plutarch’s Parallel Lives, a work with wide dissemination in the Pre-Renaissance and the Golden Age in Spain, can be the direct source for El robo de las sabinas (The Abduction of the Sabine Women), a comedy by Francisco de Rojas Zorrilla, Juan Coello y Arias and Antonio Coello Ochoa. Similarly, the paper analyses how the mythemes of classical myth are evident, mainly: the mytheme of the founding of Rome and Remus’ killing, the mytheme of the abduction of the Sabine women, the Tarpeia’s betrayal mytheme and, finally, the mytheme of the signing of peace.
Keywords: Plutarch; Antonio Coello; Juan Coello; Francisco de Rojas Zorrilla; Baroque drama; myth criticism